2023
DOI: 10.3389/fcvm.2023.1244137
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of cavotricuspid isthmus ablation using exclusive intracardiac echocardiography guidance: a proof-of-concept, observational trial

Dorottya Debreceni,
Kristof-Ferenc Janosi,
Marton Turcsan
et al.

Abstract: IntroductionCatheter ablation is the preferred treatment for typical atrial flutter (AFl), but it can be challenging due to anatomical abnormalities. The use of 3D electroanatomical mapping systems (EAMS) has reduced fluoroscopy exposure during AFl ablation. Intracardiac echocardiography (ICE) has also shown benefits in reducing radiation exposure during AFl ablation. However, there is a lack of evidence on the feasibility of ICE-guided, zero-fluoroscopy AFl ablation without the use of EAMS.MethodsIn this pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In the last years, guidance by ICE has demonstrated reducing not only fluoroscopy times but also ablation and procedure times ( 31 ) and allowing successful ablation in some challenging cases ( 32 ). More recently, zero-fluoroscopy guided exclusively by ICE has been described in two studies ( 10 , 33 ) as an effective and safe approach, without impacting procedural times and helping to recognize early potential complications. Thus, ICE could constitute a valuable alternative for zero-fluoroscopy CTI ablation, but further and larger studies are needed to confirm these preliminary findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last years, guidance by ICE has demonstrated reducing not only fluoroscopy times but also ablation and procedure times ( 31 ) and allowing successful ablation in some challenging cases ( 32 ). More recently, zero-fluoroscopy guided exclusively by ICE has been described in two studies ( 10 , 33 ) as an effective and safe approach, without impacting procedural times and helping to recognize early potential complications. Thus, ICE could constitute a valuable alternative for zero-fluoroscopy CTI ablation, but further and larger studies are needed to confirm these preliminary findings.…”
Section: Discussionmentioning
confidence: 99%
“…Given that there is a definite risk of cancer induction ( 7 ) and no minimum safe threshold dose, the radiation dose should be reduced to the lowest possible following the ALARA principle (As Low As Reasonably Achievable). As a matter of fact, the awareness of the ionizing radiation risks has led many electrophysiologists to erase the use of X-rays, by implementing zero-fluoroscopy procedures guided by electroanatomical navigation systems ( 8 , 9 ) and more recently, intracardiac echocardiography (ICE) ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have investigated the feasibility and safety of zero-fluoroscopy CTI ablation under the guidance of ICE alone [ 94 , 95 ]. Luani et al .…”
Section: Fluoroless or Near Fluoroless Ep Proceduresmentioning
confidence: 99%
“…Debreceni et al . [ 94 ] conducted a comparative study and reported a significant reduction in CTI ablation time under the sole guidance of ICE. The procedure time, puncture-to-first-ablation time, and total ablation energy in the ICE-guided group were similar to those in the fluoroscopy + ICE-guided group [ 94 ].…”
Section: Fluoroless or Near Fluoroless Ep Proceduresmentioning
confidence: 99%